2003
DOI: 10.1046/j.1365-3148.2003.00455.x
|View full text |Cite
|
Sign up to set email alerts
|

Donor exposure rate to transfusion ratio: a better discriminator of improvement in neonatal transfusion practice

Abstract: This study identifies the benefit of using donor exposure rate (DER) to transfusion rate (TR) ratio as a discriminative index for assessing improvement in practice pattern in multiple-transfused neonates. It provides a methodology to demonstrate reduction in donor exposure that is not evident from the use of DER alone. Two time points, one 12-month period (1996-1997) before and one 12-month period (1999-2000) following the introduction of a paedipack system, were reviewed. Blood issued and wasted was quantifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 11 publications
1
14
0
1
Order By: Relevance
“…In our study, each unit of RBC stored up to 28 days allowed 3·4 transfusions, and discarded RBC volume analysis at the Blood Center showed that blood waste was three‐fold higher in Group 2. Such data were similar to those seen by Ibojie et al . (2003), who reported a 70·5% reduction in blood donor exposure and decreased blood waste (from 190·0 ± 30·0 to 24·5 ± 10·0 mL per transfusion), following implementation of the paedipack system using satellite bags stored for 35 days.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, each unit of RBC stored up to 28 days allowed 3·4 transfusions, and discarded RBC volume analysis at the Blood Center showed that blood waste was three‐fold higher in Group 2. Such data were similar to those seen by Ibojie et al . (2003), who reported a 70·5% reduction in blood donor exposure and decreased blood waste (from 190·0 ± 30·0 to 24·5 ± 10·0 mL per transfusion), following implementation of the paedipack system using satellite bags stored for 35 days.…”
Section: Discussionsupporting
confidence: 93%
“…Recommendations for use include the following: a hematocrit (Hct) of less than 40% in infants on assisted ventilation or with severe cardiopulmonary disease; a Hct of less than 30% in infants with tachypnea, tachycardia, diminished activity, episodes of apnea and poor weight gain; and/or phlebotomy losses accounting for 5-10% of the infant's total blood volume. TR (average number of transfusions per infant) and DER (average number of donors to whom an infant is exposed) were calculated [4,11]. The same parameters were calculated for hypothetical use of blood satellite packs for transfusions in the analyzed patients and compared with the original data.…”
Section: Methodsmentioning
confidence: 99%
“…The complications, such as infections (hepatitis, cytomegalovirus, HIV, bacterial) [3], graft versus host disease (GvHD), and metabolic disorders, are the same in every age group. Their probability increases with the number of transfusions and donors, that is, with the transfusion rate (TR) and donor exposure rate (DER) [4]. The latter parameter depends on the pattern of transfusion.…”
Section: Introductionmentioning
confidence: 99%
“…For (preterm) neonates, but not for fetuses, transfusion programs to minimize donor exposure have already been developed and reducing donor exposure and RBC wastage is reported . This was realized by splitting normal size RBCs in series of pedipacks that are stored and designated for one patient.…”
mentioning
confidence: 99%
“…For (preterm) neonates, but not for fetuses, transfusion programs to minimize donor exposure have already been developed and reducing donor exposure and RBC wastage is reported. 5,6 This was realized by splitting normal size RBCs in series of pedipacks that are stored and designated for one patient. While IUT needs fresh RBCs, a strategy to improve matching and reduce donor exposure, would be to select a compatible donor (for C, c, D, E, e, K, Fy a , Fy b , Jk a , Jk b , M, S, and s antigens) from the large donor pool for the whole IUT treatment period of a fetus, instead of matching within a limited number of available fresh RBCs on the shelf.…”
mentioning
confidence: 99%